Service Quality, Brand Image, Customer Satisfaction, and Customer Loyalty towards Telecommunications Service Providers in Malaysia: A PLS-SEM Approach - Wan Rasyidah Wan Nawang; Salehuddin Che Murat; Intan Fatimah Anwar; Nor Haziah Hashim (Human Resource Management Academic Research Society, 2024)
Indexed by ERA